Cryopreservation impairs 3-D migration and cytotoxicity of natural killer cells - Mark, Christoph; Czerwinski, Tina; Roessner, Susanne; Mainka, Astrid; Hörsch, Franziska; Heublein, Lucas; Winterl, Alexander; Sanokowski, Sebastian; Richter, Sebastian; Bauer, Nina; Angelini, Thomas E.; Schuler, Gerold; et al. (Nature Communications, 2020)
Natural killer (NK) cells are important effector cells in the immune response to cancer. Clinical trials on adoptively transferred NK cells in patients with solid tumors, however, have thus far been unsuccessful. As NK cells need to pass stringent safety evaluation tests before clinical use, the cells are cryopreserved to bridge the necessary evaluation time. Standard degranulation and chromium release cytotoxicity assays confirm the ability of cryopreserved NK cells to kill target cells. Here, we report that tumor cells embedded in a 3-dimensional collagen gel, however, are killed by cryopreserved NK cells at a 5.6-fold lower rate compared to fresh NK cells. This difference is mainly caused by a 6-fold decrease in the fraction of motile NK cells after cryopreservation. These findings may explain the persistent failure of NK cell therapy in patients with solid tumors and highlight the crucial role of a 3-D environment for testing NK cell function.
CRIS-Team Scopus Importer:2020-10-23

Detecting long-range interactions between migrating cells - Metzner, C.; Hörsch, F.; Mark, Christoph; Czerwinski, Tina; Winterl, Alexander; Voskens, Caroline; Fabry, Ben (Scientific Reports, 2021)
Chemotaxis enables cells to systematically approach distant targets that emit a diffusible guiding substance. However, the visual observation of an encounter between a cell and a target does not necessarily indicate the presence of a chemotactic approach mechanism, as even a blindly migrating cell can come across a target by chance. To distinguish between the chemotactic approach and blind migration, we present an objective method that is based on the analysis of time-lapse recorded cell migration trajectories: For each movement step of a cell relative to the position of a potential target, we compute a p value that quantifies the likelihood of the movement direction under the null-hypothesis of blind migration. The resulting distribution of p values, pooled over all recorded cell trajectories, is then compared to an ensemble of reference distributions in which the positions of targets are randomized. First, we validate our method with simulated data, demonstrating that it reliably detects the presence or absence of remote cell-cell interactions. In a second step, we apply the method to data from three-dimensional collagen gels, interspersed with highly migratory natural killer (NK) cells that were derived from two different human donors. We find for one of the donors an attractive interaction between the NK cells, pointing to a cooperative behavior of these immune cells. When adding nearly stationary K562 tumor cells to the system, we find a repulsive interaction between K562 and NK cells for one of the donors. By contrast, we find attractive interactions between NK cells and an IL-15-secreting variant of K562 tumor cells. We therefore speculate that NK cells find wild-type tumor cells only by chance, but are programmed to leave a target quickly after a close encounter. We provide a freely available Python implementation of our p value method that can serve as a general tool for detecting long-range interactions in collective systems of self-driven agents.
CRIS-Team Scopus Importer:2021-08-06

Dynamic traction force measurements of migrating immune cells in 3D biopolymer matrices - Böhringer, David; Cóndor, Mar; Bischof, Lars; Czerwinski, Tina; Gampl, Niklas; Ngo, Phuong; Bauer, Andreas; Bosch-Voskens, Caroline; Lopez Posadas, Rocío; Franze, Kristian; Budday, Silvia; Mark, Christoph; et al. (Nature Physics, 2024)
Immune cells, such as natural killer cells, migrate with high speeds of several micrometres per minute through dense tissue. However, the magnitude of the traction forces during this migration is unknown. Here we present a method to measure dynamic traction forces of fast migrating cells in biopolymer matrices from the observed matrix deformations. Our method accounts for the mechanical nonlinearity of the three-dimensional tissue matrix and can be applied to time series of confocal or bright-field image stacks. It allows for precise force reconstruction over a wide range of force magnitudes and object sizes—even when the imaged volume captures only a small part of the matrix deformation field. We demonstrate the broad applicability of our method by measuring forces from around 1 nN for axon growth cones up to around 10 μN for mouse intestinal organoids. We find that natural killer cells show bursts of large traction forces around 50 nN that increase with matrix stiffness. These force bursts are driven by myosin II contractility, mediated by integrin β1 adhesions, focal adhesion kinase and Rho-kinase activity, and occur predominantly when the cells migrate through narrow matrix pores.
CRIS-Team Scopus Importer:2024-11-29

Ex vivo expanded NK Cells from Melanoma Patients receive their Migration in a 3D Model and lyse autologous Melanoma Cells - Rossner, S.; Czerwinski, Tina; Mark, Christoph; Gross, S.; Karg, Margarete; Bosch, Jacobus J.; Schuler-Thurner, Beatrice; Fabry, Ben; Schuler, Gerold; Bosch-Voskens, C. (2018)
EVALuna2:34775

Increased Motility and Suppression of Ex Vivo–Expanded Regulatory T Cells Designed for Adoptive Transfer Therapy in Ulcerative Colitis - Müller, Tanja; Liu, Lijuan; Czerwinski, Tina; Wiesinger, Manuel; Dedden, Mark; Paap, Eva-Maria; Ullrich, Karen; Atreya, Imke; Siegmund, Britta; Atreya, Raja; Fabry, Ben; Berking, Carola; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2023)
CRIS-Team Scopus Importer:2023-06-02

Mesenchymal-Like Migration Strategies of Immune Cells in a 3D Environment - Czerwinski, Tina; Mark, Christoph; Roessner, Susanne; Bosch-Voskens, Caroline; Bhattacharjee, Tapomoy; Angelini, Thomas E.; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

NR4A1 Regulates Motility of Osteoclast Precursors and Serves as Target for the Modulation of Systemic Bone Turnover - Scholtysek, Carina; Ipseiz, Natacha; Böhm, Christina; Krishnacoumar, Brenda; Stenzel, Martin; Czerwinski, Tina; Palumbo-Zerr, Katrin; Rothe, Tobias; Weidner, Daniela; Klej, Alexandra; Stoll, Cornelia; Distler, Jörg; et al. (Journal of Bone and Mineral Research, 2018)
NR4A1 (Nur77 or NGFI-B), an orphan member of the nuclear receptor superfamily, has been identified as a key regulator of the differentiation and function of myeloid, lymphoid, and mesenchymal cells. The detailed role of NR4A1 in bone biology is incompletely understood. Here, we report a role for NR4A1 as novel factor controlling the migration and recruitment of osteoclast precursors during bone remodeling. Myeloid-specific but not osteoblast-specific deletion of NR4A1 resulted in osteopenia due to an increase in the number of bone-lining osteoclasts. Although NR4A1-deficient osteoclast precursors displayed a regular differentiation into mature osteoclasts, they showed a hyper-motile phenotype that was largely dependent on increased osteopontin expression, suggesting that expression of NR4A1 negatively controlled osteopontin-mediated recruitment of osteoclast precursors to the trabecular bone. Pharmacological activation of NR4A1, in turn, inhibited osteopontin expression and osteopontin-dependent migration of osteoclast precursors resulted in reduced abundance of bone-resorbing osteoclasts in vivo as well as in an ameliorated bone loss after ovariectomy in mice. This study identifies NR4A1 as a crucial player in the regulation of osteoclast biology and bone remodeling and highlights this nuclear receptor as a promising target for therapeutic intervention during the treatment of osteoporosis. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.
EVALuna2:34484